Kriminologis Terhadap Tindak Pidana Korupsi Dana Desa - Tirande, Darwis; Nirahua, Salmon Eliazer Marthen; Toule, Elsa Rina Maya (PATTIMURA Legal Journal, 2022)
Introduction: Criminology makes a very large contribution to criminal law, by revealing the factors that cause corruption Purposes of the Research: This research also aims to, first; Analyze and explain the factors that cause corruption in village funds in Maluku, secondly; Analyze and explain efforts to overcome corruption in village funds in Maluku. Methods of the Research: The type of research used is normative law research using a statutory approach (Statute Apporach), conceptual approach (Conceptual Apporach) and case approach (Case Apporach). While the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Results Originality of the Research: Based on the results of the study, the factors causing the occurrence of corruption in village fund funds were caused by various factors including regulatory factors that gave broad authority to village heads in managing village funds, as well as village heads who did not know how to manage village funds properly so that ignorance led to what they are doing without realizing that it is a criminal act of corruption and lack of community participation in controlling the management of village funds, therefore the effort that must be made is to carry out preventive efforts as a preventive measure by recognizing the modus operandi, training by the village head and improving personality to villages and improve the community environment so that they participate in supervising village funds, while repressive efforts are to prioritize law enforcement and provide guidance to village heads who have committed criminal acts of corruption